6.1k views
4 votes
Simplify 5(x-4)+3x-9x+7. Show your work.


2 Answers

2 votes

Answer: -x-13

Explanation:

1. Collect like terms

5(x-4)+(3x-9x)+7

2. Simplify

5(x-4)-6x+7

3. Expand

5x-20-6x+7

4. Collect like terms

(5x+6x)(-20+7)

5. Simplify

-x-13

Hope this helps, have a BLESSED day! :-)

User CJLam
by
6.1k points
6 votes

5(x-4)+3x-9x+7

mutiply the bracket by 5

(5)(x)= 5x

(5)(-4)= -20

5x-20+3x-9x+7

5x+3x-9x-20+7 ( combine like terms)

do 5x+3x first

5x+3x= 8x

8x-9x-20+7

8x-9x= -x

-20+7=-13

answer:

-x-13 or -13-x

User Fadi
by
5.6k points